Cloud Computing Implementation Using LXD in Operating System Course at Caltex Riau Polytechnic - Muhammad Arif Fadhly Ridha; Rahmat Suhatman (DISTANCE: Journal of Data Science, Technology, and Computer Science, 2021)
There are many virtualization technologies currently available, one of which is LXD on the Linux operating system. LXD can be used to build a Private Cloud. Currently, the operating system practicum lectures at Caltex Riau Polytechnic are still using Virtualization Software such as VMWare or Virtualbox which often cause problems such as virus threats, data loss, and configuration errors. For this reason, it is necessary to design and implement a centralized system using cloud computing and virtualization so that these problems can be avoided. The Cloud Computing system was created using LXD with the configuration that each student will have a virtual server account on the Cloud System. From the tests carried out, it was found that LXD can be used for operating system lecture with a memory requirement of 7.6GB with 20% CPU usage.